DESAIN DAN IMPLEMENTASI APLIKASI SIMULASI TOEFL MENGGUNAKAN ALGORITA RANDOM NUMBER GENERATOR BERBASIS WEB - Muh Istikmal Husain; Gunawan; Budi Wijaya Rauf (Program Studi Ilmu Komputer FMIPA-UHO, 2025)
This research aims to develop a web-based TOEFL simulation application system using the RNG algorithm to randomize questions. The study was conducted using three different scenarios for different test types (listening, reading, and structure). The first scenario involved 10 trials for each test type to test the consistency and randomness of the algorithm used. The second test scenario was conducted to assess the quality of randomization when there was a large amount of data in the question bank stored in the database. The third test scenario was conducted to examine the results of randomization when there were two users with the same access time but different user IDs. The randomization process was carried out through a previously designed web application and used the MCG equation, one of the methods in the RNG algorithm. The results of the research conducted indicate that the use of the RNG algorithm using the MCG method can be applied well to the TOEFL simulation system. For example, the results of the first scenario test showed that in each trial, the resulting question order was different. For example, in the structure test, a question with a certain number may appear in position 18 on the first trial, but in subsequent trials it may shift to position 27 or 32; The test results also found that even though both users had the same access time, differences in User ID values caused different initial seed values. This small difference in seed values resulted in a significantly different question order.